INFORMATION ON DEVELOPMENT 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
INFORMATION ON DEVELOPMENT Mr llunga Bamayeja, Bonnes Oeuvres Chretiennes d'Afrique, Lubumbashi, Zaire: 'We would be guilty of ingratitude if we failed to record our appreciation of your help in expanding our activities. Many thingshave changed in...